Effect of a physical therapy protocol on the health related quality of life of patients with temporomandibular disorder - Maíra de Oliveira Viana; Natália Bitar da Cunha Olegario; Mariana de Oliveira Viana; Guilherme Pinheiro Ferreira da Silva; Jair Licio Ferreira Santos; Sarah Tarcisia Rebelo Ferreira de Carvalho (Fisioterapia em Movimento)
Abstract Introduction: Temporomandibular disorders (TMD) comprise a group of diseases that affect not only the temporomandibular joint, but also different areas extrinsic to the joints. Quality of life has been the subject of numerous studies in the Health area, especially aimed at people with chronic diseases, such as TMD. Objective: To evaluate effects of a physical therapy protocol on the quality of life of patients with temporomandibular disorder. Methods: Blinded, prospective, clinical trial, with 60 patients of both genders, aged between 18 and 70 years with TMD diagnosis attended in the clinic of Ribeirão Preto School of Dentistry. The patients were divided into two groups, with one group, in addition to dental treatment, receiving a physical therapy protocol and the other group dental treatment only, for 5 weeks. The measurement of quality of life was obtained through the generic SF-36 questionnaire, at the beginning and end of the proposed protocol. Results: The patients to whom the physical therapy protocol was applied associated with dental care presented increased scores in all the domains of the questionnaire. In the group that received only dental treatment, improvements were only found in the domain related to pain. Conclusion: The application of a physical therapy protocol was able to improve the quality of life of patients with temporomandibular disorder.